Ethnic advertising: adolescents' attitudes towards target and non-target advertisements - Muhammad Mohsin, Butt; Ernest Cyril, de Run (Emerald Group Publishing Limited, 2010)
The results indicate a significant group difference between target and non-target respondents to the advertisement. It also shows that ethnicity is a viable target variable for both majority and minority ethnic groups in Malaysia.